Is Eliphaz a false prophet? The vision in Job 4.12-21 - Burnight, John (2021)
The night vision recounted by Job’s friend Eliphaz in Job 4.12-21 has received an extraordinary amount of scholarly attention. Among other difficulties, the core of the vision’s message (4.17) – typically interpreted as stating that humans cannot be just in God’s sight – appears to contradict Eliphaz’s statements elsewhere (e.g., 4.6-7). The relationship between 4.17 and the metaphors for death with which the vision ends has also occasioned considerable debate.In this paper, it is argued that Eliphaz’s words can be viewed as a response to Job’s speech in Chapter 3, particularly his description of the sleep of death in 3.11-19. The poet portrays Eliphaz as having perceived Job’s words as a challenge to God’s justice and has him—after implying divine inspiration for his message with the use of an extraordinary set of oracular tropes in vv. 12-16—offer in vv. 17-21 a rebuke and warning evocative of those used by biblical prophets to call sinners to repentance. As the prologue indicates, however, Job’s suffering is not due to sin but instead to his superlative goodness; Eliphaz’s words are therefore profoundly misguided and can have no salutary effect.In essence, I propose that the poet is presenting Eliphaz as an example of what Deut. 18.20 calls a ‘presumptuous prophet’, that is, one who wrongly claims that he is speaking on behalf of God. His remarks serve only to distance Job further from both the ‘friends’ and God, as Job’s sharper tone in Chapters 6-7 makes clear. This reading can help explain some of the more puzzling elements in these verses and also maintains the traditional attribution of the vision to Eliphaz (instead of to Job himself, as a growing number of scholars have proposed).
Keywords: Eliphaz; Hebrew Poetry; Job 4; Eliphaz; Book of Job; Hebrew Bible